Cars on mars : Roving the red planet - Siy, Alexandra (Watertown : Charlesbridge, 2009)
Follow the course of NASA's Mars Exploration Rovers Mission. Learn how scientists determined that there was once water on Mars and how they resolved problems with the rovers in order to prolong the mission.
Keywords: Mars (Planet) -Exploration -- Juvenile literature; Roving vehicles( Astronautics ) -- Juvenile literature